(untitled) (Sciences & Technology. A, exactes sciences, 2001)
In this paper, a modified Monte Carlo simulation is developed for studying grain growth in presence of stable incoherent particles. The aim is to introduce the calculation method (with C++) applied to the particles problem, to pick out the grain local behavior, to evaluate the grain growth exponent and to determine the abrupt transition between normal and stagnant microstructure. We deal with 2D microstructures with a constant particle diameter and different particle area fraction.